"n Ondersoek na die teologiese relevansie van die metaforiese spreke in Hooglied - Basson, M. M. J. (Hervormde teologiese studies, 1995)
An inquiry into the problem of theological relevance, posed by the metaphors in the Song of Songs. Of the six basic scholarly approaches to the Song of Songs, the literary approach is today most widely accepted. This approach still however does not give all the answers to the problem of an evasive theological relevance, posed by the metaphors in the Song of Songs. This article argues that a certain perspective on metaphors will open up new ways of understanding the Song. When this perspective is coalesced with narratology, results are reached that will certainly enhance this celebrated poem.